Have lessons from past failures brought us closer to the success of immunotherapy in metastatic pancreatic cancer? - Laura Rosa Brunet; Thorsten Hagemann; Andrew Gaya; Satvinder Mudan; Aurelien Marabelle (OncoImmunology)
Pancreatic cancer is extremely resistant to chemo- and radiation-therapies due to its inherent genetic instability, the local immunosuppressive microenvironment and the remarkable desmoplastic stromal changes which characterize this cancer. Therefore, there is an urgent need for improvement on standard current therapeutic options. Immunotherapies aimed at harnessing endogenous antitumor immunity have shown promise in multiple tumor types. In this review, we give an overview of new immune-related therapeutic strategies currently being tested in clinical trials in pancreatic cancer. We propose that immunotherapeutic strategies in combination with current therapies may offer new hopes in this most deadly disease.